HERMENEUTIC LANGUAGE STYLE IN THE POEM â€œPESAN PENCOPET KEPADA PACARNYAâ€ BY W S RENDRA (SEMIOSTYLISTIC STUDY) - Irham Thufani Anshori (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Poem is a form of written literature which is mostly written using the style of hermeneutic language in it. One of the poems that contains a lot of hermeneutic style is a poem by WS Rendra entitled â€œPesan Pencopet kepada Pacarnyaâ€ which is the object of research in this research. Pesan pencopet kepada pacarnya carries a lot of social criticism made by Rendra against social inequality that occurs in society by using many semiostylistic elements in his writing. This study was structured with the aim of knowing the meaning of hermeneutic figurative language in the poem Pesan Pencopet kepada Pacarnya by W S Rendra using semiostylistic study theory. This study uses a qualitative approach based on data sources and research data is the poem Pesan Pencopet kepada Pacarnya by W S Rendra. Data collection techniques in this study used literature study techniques. The results of this study indicate that through the interpretation of the meaning of hermeneutic style in this poem has a content of critical meaning or Rendra's views and concerns about problems and social imbalances that occur in society, related to the fate of lowly people, morality, promiscuity, to his criticism of officials. Which in almost every stanza of his poetry, Rendra uses many semiotic signs with stylistic language styles in writing these poems. Furthermore, the meaning and process of subjective interpretation of this poem are effectively carried out through an analysis of the meaning of the hermeneutic style of language in each stanza and poem.